1994
DOI: 10.1093/oxfordjournals.aje.a117029
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Factors and Gastric Cancer in Spain

Abstract: A case-control study on diet and gastric cancer, carried out in selected areas of four regions of Spain (Aragon, Castile, Catalonia, and Galicia) in 1988 and 1989, included 354 cases of histologically confirmed gastric adenocarcinoma and 354 controls matched by age, sex, and area of residence. Cases and controls were selected from 15 hospitals, representing most of the hospital facilities in the study areas. Usual diet was estimated by means of a dietary history questionnaire administered by interview. An incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
57
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(65 citation statements)
references
References 12 publications
7
57
0
Order By: Relevance
“…Of the previous studies, all of them case -control, that have considered GC pathology in relation to dietary carotenoids, some have failed to detect any associations or differences by subtype (Boeing et al, 1991;Buiatti et al, 1991), whereas others have shown mixed results (Gonzalez et al, 1994;Harrison et al, 1997;Ekstrom et al, 2000), suggesting that the effects of carotenoids might be similar in both histological subtypes. In the present study, none of the analytes, with the possible exception of a-tocopherol, showed any significant effects by anatomical subsite or histological subtype.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of the previous studies, all of them case -control, that have considered GC pathology in relation to dietary carotenoids, some have failed to detect any associations or differences by subtype (Boeing et al, 1991;Buiatti et al, 1991), whereas others have shown mixed results (Gonzalez et al, 1994;Harrison et al, 1997;Ekstrom et al, 2000), suggesting that the effects of carotenoids might be similar in both histological subtypes. In the present study, none of the analytes, with the possible exception of a-tocopherol, showed any significant effects by anatomical subsite or histological subtype.…”
Section: Discussionmentioning
confidence: 96%
“…Several case -control studies have shown strong inverse associations between GC risk and higher consumption of some of these nutrients (Buiatti et al, 1990(Buiatti et al, , 1991Gonzalez et al, 1994;Hansson et al, 1994;Ekstrom et al, 2000). Results from prospective dietary studies are conflicting and show either a strong protection (Zheng et al, 1995) or no clear inverse associations between the dietary intake of carotenoids and GC risk (Ocke et al, 1995;Botterweck et al, 2000b).…”
mentioning
confidence: 99%
“…In most studies a statistically significant inverse association was reported between nitrate intake from foods and gastric cancer risk (Risch et al, 1985;Buiatti et al, 1990;Boeing et al, 1991;Gonzalez et al, 1994;Hansson et al, 1994;La Vecchia et al, 1994), which disappeared after additional adjustment for potential confounders (mainly intake of vitamin C and beta-carotene). In all case-control studies on nitrate and gastric cancer risk, a positive association was reported (Risch et al, 1985;Buiatti et al, 1990;Gonzalez et al, 1994;Hansson et al, 1994;La Vecchia et al, 1994;Pobel et al, 1995) which reduced after adjustment for intake of other nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Case-control studies have mainly investigated the association between nitrate or nitrite from foods and gastric cancer risk (Risch et al, 1985;Buiatti et al, 1990;Boeing et al, 1991;Palli et al, 1992;Gonzalez et al, 1994;Hansson et al, 1994;La Vecchia et al, 1994;Pobel et al, 1995). In most studies a statistically significant inverse association was reported between nitrate intake from foods and gastric cancer risk (Risch et al, 1985;Buiatti et al, 1990;Boeing et al, 1991;Gonzalez et al, 1994;Hansson et al, 1994;La Vecchia et al, 1994), which disappeared after additional adjustment for potential confounders (mainly intake of vitamin C and beta-carotene).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation